Analisis Pertanggungjawaban Pidana Anak Sebagai Pelaku Tindak Pidana Pencabulan - Nasution, Idris (Program Studi Hukum Keluarga Islam STAIN Mandailing Natal, 2020)
ABSTRACTION IDRIS The responsibility of a crime is a case that must be responsible by the doer that has done the crime, although the doer is an adult or a child. One of the sample in a decision No. 8/Pid.Sus-Anak/2015/PN.Tjb, the doer is a child, namely Dicky Donatus Situmorang, 17 years old. The defendant has a validity and assured proven in doing desecrate to injustice to someone consciously in doing the desecrate injustice although is known or should be anticipated that the victim is 15 years old. He can not be married, an the doer in consciousness doing a gimmic for doing it. The case in this study is how to arrange the punishment for child as a pretrator in a desecrate injustice, what is the reason factor to a child to do a desecrate injustice and what is the law policy crime for that case no. 8/Pid.Sus-Anak/2015/PN.Tjb. Whatever the decision has fulfil the sense of the justice.The study is done by using yuridis normative and yuridis empire approach. The source of the study is divided into primary and secondary data. The primary data which is gotten from the field research, that is by giving an interview to one of the child judge. In Tanjung Balai. The secondary data is gotten from library research by checking and correcting data , after the data is processed and analysed by using qualitative analysing.Based on the result and solution in the responsibility for child as a Perpetrator in doing a desecrate injustice in the court decision no : 8/Pid.Sus-Anak/2015/PN.Tjb, namely the doer has a validity and insure evident in conducted action against the criminal law , that is section 82 Undang-Undang No 35 Tahun 2014 in child protection. The doer can be gotten the responsibility for the crime that he has done because in case has a fault and fulfil the element in doing injustice.The judge cares about the doer is a child, the regulation which arrange the child regulation, so the judge punished the child 2 years in prison, an 2 months grounding. The decision of the judge is not fulfil the sense of judgement because the judge punished the child 2 years in prison, an 2 months grounding. The suggestion in the research should be given and educated to the family for getting extra action , dont be punished in prison and 2 months grounding. The suggestion, the judge should think norm of the justice for all not only for the victim but also to the doer, and society and decision maker, and law government officer. Key Word : The Responsibility of the Child Crime as A Perpetrator in Doing A Desecrate Injustice.